Dietary analysis reveals differences in the prey use of two sympatric bat species - Heim Olga; Puisto Anna I.E; Sääksjärvi Ilari; Fukui Dai; Vesterinen Eero J. (Wiley-Blackwell, 2022)
One mechanism for morphologically similar and sympatric species to avoid competition and facilitate coexistence is to feed on different prey items within different microhabitats. In the current study, we investigated and compared the diet of the two most common and similar-sized bat species in Japan—Murina ussuriensis (Ognev, 1913) and Myotis ikonnikovi (Ognev, 1912)—to gain more knowledge about the degree of overlap in their diet and their foraging behavior. We found that both bat species consumed prey from the orders of Lepidoptera and Diptera most frequently, while the proportion of Dipterans was higher in the diet of M. ikonnikovi. Furthermore, we found a higher prey diversity in the diet of M. ikonnikovi compared to that of M. ussuriensis that might indicate that the former is a more generalist predator than the latter. In contrast, the diet of M. ussuriensis contained many Lepidopteran families. The higher probability of prey items likely captured via gleaning to occur in the diet of M. ussuriensis in contrast to M. ikonnikovi indicates that M. ussuriensis might switch between aerial-hawking and gleaning modes of foraging behavior. We encourage further studies across various types of habitats and seasons to investigate the flexibility of the diet composition and foraging behavior of these two bat species.